2005
DOI: 10.1186/1476-511x-4-21
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia in men with metabolic syndrome, hypertensives and healthy subjects

Abstract: BackgroundThe metabolic syndrome (MetS), as well as postprandial hypertriglyceridemia, is associated with coronary heart disease. This study aimed to evaluate the postprandial lipemia after oral fat tolerance test (OFTT) in subjects with MetS and compare them to hypertensive (HTN) and healthy subjects.ResultsOFTT was given to 33 men with MetS (defined by the Adult Treatment Panel III), 17 HTN and 14 healthy men. The MetS group was further divided according to fasting triglycerides (TG) into TG ≥ 150 [MetS+TG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 42 publications
2
23
2
3
Order By: Relevance
“…In contrast to our results, other studies including individuals with diverse cardiovascular risk have reported that fasting triglycerides levels is the major determinant of postprandial lipemia [ 3 , 5 , 6 , 20 ]. The novel finding of an independent association between fasting apo B-48 levels and postprandial lipemia in FCH indicate a potential role for intestinal-derived lipoproteins in postprandial metabolism in individuals with FCH.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, other studies including individuals with diverse cardiovascular risk have reported that fasting triglycerides levels is the major determinant of postprandial lipemia [ 3 , 5 , 6 , 20 ]. The novel finding of an independent association between fasting apo B-48 levels and postprandial lipemia in FCH indicate a potential role for intestinal-derived lipoproteins in postprandial metabolism in individuals with FCH.…”
Section: Discussioncontrasting
confidence: 99%
“…The metabolic syndrome, a clustering of several abnormalities including fasting hypertriglyceridemia, is associated with abnormal postprandial lipemia [16,73,74]. In hypercholesterolemic patients with the metabolic syndrome, simvastatin and atorvastatin had comparable beneficial effects on apolipoprotein B-containing atherogenic lipids and lipoproteins, and metabolic syndrome status was effectively modified by both drugs.…”
Section: Statinsmentioning
confidence: 97%
“…Results obtained with the minimum sample size calculations corroborate this suggestion, since the supplementation with pequi capsules reduced the variability of the sample and, consequently, the required sample size. Other reports with lower or equal intervention times have also shown physiological effects, with significant changes in the used markers [51,52,53,54,55]. …”
Section: Discussionmentioning
confidence: 99%